2017
DOI: 10.1155/2017/7168687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia on the Differentiation and the Self-Renewal of Metanephrogenic Mesenchymal Stem Cells

Abstract: Hypoxia is an important and influential factor in development. The embryonic kidney is exposed to a hypoxic environment throughout its development. The Wnt/β-catenin pathway plays vital roles in the differentiation and self-renewal of metanephrogenic mesenchymal stem cells (MMSCs) from which the kidney is derived. Thus, we hypothesized that hypoxia can regulate the differentiation and pluripotency of MMSCs through the Wnt/β-catenin pathway. To test this hypothesis, MMSCs from rats at embryonic day 18.5 were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Previous study has shown that the hypoxia and HGF treatment enhance the differentiation of umbilical cord blood-derived stromal cells into IPCs (Sun et al, 2015 ). Additionally, hypoxic conditions promoted the differentiation and depressed the self-renewal of metanephrogenic mesenchymal stem cells (Liu et al, 2017 ). In contrast, there is evidence that oxygen influences the different cell subsets during pancreatic development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that the hypoxia and HGF treatment enhance the differentiation of umbilical cord blood-derived stromal cells into IPCs (Sun et al, 2015 ). Additionally, hypoxic conditions promoted the differentiation and depressed the self-renewal of metanephrogenic mesenchymal stem cells (Liu et al, 2017 ). In contrast, there is evidence that oxygen influences the different cell subsets during pancreatic development.…”
Section: Discussionmentioning
confidence: 99%
“…SC are multipotent cells, and depending on the stimuli and stress type, duration, and severity, they can follow myogenic, adipogenic, or osteogenic pathways ( Asakura et al., 2001 ; Shefer et al., 2004 ; Wang et al., 2015a ; Liu et al., 2017 ). As WB is characterized by infiltration of fat cells, we sought to evaluate here the potential activation of adipogenic program in SC under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle satellite cells ( SC ), stem cells located between the basement membrane and sarcolemma of muscle fiber ( Moss and Leblond, 1971 ), are self-renewing mesenchymal cells that enable hypertrophy, maintenance, and repair of damaged skeletal muscle ( Geiger et al., 2018 ). It has been shown that SC are multipotent and can be induced by various extrinsic factors and environment to follow myogenic, adipogenic, or osteogenic pathways ( Asakura et al., 2001 ; Wang et al., 2015a ; Liu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that mGSCs preferentially reside in hypoxic regions of the ST, which facilitates metabolic pathways that are integral for the ongoing regenerative capacity of the cells [23]. Though bene cial effects of hypoxic culture on proliferation and differentiation potentials of speci c cell lines have been suggested by several groups [12,27,19], other studies showed contrasting results with negative or no effects of hypoxia on stem cell proliferation and differentiation [2,21]. These discrepancies in the results may be due to the variation in the O 2 level, the duration of trial, range of biological characteristics compared with type and number of stem cell population, and the variation in the sensitivity of system that was used to regulate the O 2 level.…”
Section: Discussionmentioning
confidence: 99%